Barriers and Facilitators of Using Clinical Guidelines for Cardiopulmonary Resuscitation from the Point of View of Emergency Department Nurses - Hossein Sadeghnezhad; Marzieh HelalBirjandi; Seyyed Abolfazl Vagharseyyedin; Ebrahim Moradi (Kerman University of Medical Sciences, 2024)
Background: Cardiopulmonary resuscitation (CPR) is an emergency method to restore blood flow and spontaneous breathing in a person who has suffered cardiac arrest. Clinical practice guidelines are recommendations for nurses regarding the care of patients with specific conditions such as cardiac arrest. Accordingly, this study aimed to investigate the experiences of hospital emergency department nurses regarding the implementation of CPR guidelines.Methods: This study was conducted using a qualitative content analysis approach to investigate the experiences of 11 emergency department nurses. The participants were selected using purposive sampling. Data were collected through in-depth semi-structured interviews until saturation was reached. Data were analyzed using the content analysis method proposed by Graneheim and Lundman simultaneously with data collection.Results: Data analysis led to the identification of two main categories and ten subcategories. The categories included "barriers" with five subcategories (lack of knowledge and skills, low motivation, work pressure, lack of facilities, and lack of cooperation among the CPR team) and "facilitators" with five subcategories (facility development, teamwork, conscientiousness, adequate training, and effective supervision).Conclusion: Nursing managers can use nurses' experiences to find appropriate ways to improve the use of clinical guidelines for CPR.